2001
DOI: 10.1046/j.1365-201x.2001.00820.x
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione deficiency intensifies ischaemia‐reperfusion induced cardiac dysfunction and oxidative stress

Abstract: The efficacy of glutathione (GSH) in protecting ischaemia-reperfusion (I-R) induced cardiac dysfunction and myocardial oxidative stress was studied in open-chest, stunned rat heart model. Female Sprague-Dawley rats were randomly divided into three experimental groups: (1) GSH-depletion, by injection of buthionine sulphoxamine (BSO, 4 mmol kg(-1), i.p.) 24 h prior to I-R, (2) BSO injection (4 mmol kg(-1), i.p.) in conjunction with acivicin (AT125, 0.05 mmol kg(-1), i.v.) infusion 1 h prior to I-R, and (3) contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
38
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(41 citation statements)
references
References 40 publications
3
38
0
Order By: Relevance
“…Impaired diastolic and contractile function in G6PD def hearts is similar to the cardiac dysfunction that has previously been shown to occur during ischemia-reperfusion with depletion of cellular glutathione [7][8][9] or with inhibition of glutathione cycling. 32,33 This suggests that G6PD mediates susceptibility to ischemia-reperfusion injury through maintenance of cellular glutathione and protection against oxidative stress.…”
Section: Depletion Of Cellular Glutathione In G6pd Def Mice During Ismentioning
confidence: 49%
See 1 more Smart Citation
“…Impaired diastolic and contractile function in G6PD def hearts is similar to the cardiac dysfunction that has previously been shown to occur during ischemia-reperfusion with depletion of cellular glutathione [7][8][9] or with inhibition of glutathione cycling. 32,33 This suggests that G6PD mediates susceptibility to ischemia-reperfusion injury through maintenance of cellular glutathione and protection against oxidative stress.…”
Section: Depletion Of Cellular Glutathione In G6pd Def Mice During Ismentioning
confidence: 49%
“…5,6 GSH allows for the conversion of deleterious hydrogen peroxide and lipid peroxides to water and alcohols, respectively. 6 Depletion of cardiac GSH exacerbates myocardial ischemia-reperfusion injury, [7][8][9] whereas exogenous supplementation with GSH protects against such injury. 7,10,11 Generation of GSH from its oxidized form, GSSG, and subsequent maintenance of intracellular GSH pools require reducing equivalents in the form of the pyridine nucleotide NADPH.…”
mentioning
confidence: 99%
“…Besides acting as an electron donor to neutralize hydrogen peroxide (H 2 O 2 ) and lipoperoxide, GSH also scavenges oxygen-and nitrogenbased free radicals (Ji 1999). Based on these antioxidant properties, the effect of GSH has been extensively studied in many experimental models that induce tissue dysfunction by oxidative damage (Ji et al 1994;Leichtweis and Ji 2001), namely acute exercise, ischemiareperfusion and drug administration. With these experimental models, several authors have shown that the depletion of intrinsic GSH exacerbates tissue damage inflicted by many stimuli (Sen et al 1993;Sen et al 1994;Leeuwenburgh and Ji 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Although thrombolytic therapy and percutaneous coronary interventions reduce mortality from acute myocardial infarction, additional therapeutic strategies are needed, given that reperfusion of the ischemic myocardium generates oxygen free radicals 1,2 and that impaired myocardial antioxidant defense capacity leads to tissue injury. 3 Several clinical trials, the Randomized Aldactone Evaluation Study 4 and the Eplerenone Post-Acute Myocardial Infarction Heart Failure Efficacy and Survival Study, 5 showed decreased mortality with the use of mineralocorticoid receptor antagonists in addition to standard therapy, evidence for a role of mineralocorticoid receptor (MR) activation in myocardial infarction and heart failure. In the Eplerenone PostAcute Myocardial Infarction Heart Failure Efficacy and Survival Study, 32% of the patients were diabetic, and patients randomized early to treatment derived more benefit than those randomized later.…”
mentioning
confidence: 99%